Non-steroidal anti-inflammatory drug use does not appear to be associated with increased cardiovascular mortality in patients with inflammatory polyarthritis: results from a primary care based inception cohort of patients. Issue 3 (13th April 2008) - Goodson, N J; Brookhart, A M; Symmons, D P M; Silman, A J; Solomon, D H
Abstract : Objectives: There is controversy about the effects of non-steroidal anti-inflammatory drugs (NSAIDs) on cardiovascular disease (CVD) mortality. The aim of this study was to explore associations between NSAID use and mortality in patients with inflammatory polyarthritis (IP). Subjects and methods: A total of 923 patients with new onset (IP), recruited to the UK Norfolk Arthritis Register (NOAR) between 1990–1994, were followed up to the end of 2004. Current medication was recorded annually for the first 6 years and then every 2–3 years. Rheumatoid factor (RF) and C-reactive protein (CRP) were measured. Logistic regression was used to calculate all cause and CVD mortality odds ratios (OR) for NSAID use at baseline and during follow-up, adjusting for gender and time-varying covariates: RF, CRP, joint counts, smoking, steroid use, DMARD use and other medication use. Results: By 2004 there were 203 deaths, 85 due to CVD. At baseline, NSAIDs were used by 66% of patients. In final multivariate models, baseline NSAID use was inversely associated with all cause mortality (adjusted OR 0.62, 95% CI 0.45 to 0.84) and CVD mortality (adjusted OR 0.54, 95% CI 0.34 to 0.86). Interval NSAID use had weaker mortality associations: all cause mortality (adjusted OR 0.72, 95% CI 0.52 to 1.00), CVD mortality (adjusted hazard ratio (HR) 0.66, 95% CI 0.40 to 1.08). Conclusion: No excess CVD or all cause mortality was observed in NSAID users in this cohort of patients with IP. This is at variance with the literature relating to NSAID use in the general population. It is unclear whether this represents unmeasured confounders influencing a doctor's decision to avoid NSAIDs in the treatment of IP.